Sistem Informasi Akuntansi pada Pondok Pesantren Ahmad Dahlan Berbasis Dekstop - Sartika, Aprillia Dwi (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2019)
Financial management systems in Islamic boarding schools Ahmad Dahlan have used in the use of computers, namely by noting a financial report in and out in Microsoft Excel. But the use of devices the computers are not optimal. Due to lack of use, Microsoft excel cause to the emergence of a new problem, among others file that is stored too long susceptible to broken or corrupt. Hence the writer provides solutions by building an information system that might increase the ease of, the accuracy of and security. In addition, this accounting information system can make maximum use of computers in the management of financial data and does not require the time and place of plenty for its final resting. The methodology used is in the design of this is a waterfall with modeling UML ( The unified modeling language) as modeling graphic. There are several stages in the development of which is executed is system design, analysis, the design of a model, implementation, testing, and maintenance or care. The accounting information system is able to give a solution to the existing problems with reference to the design process that they were previously, hopefully with this application can help in processing financial data in Ahmad Dahlan Islamic boarding schools.